A preliminary investigation of the relationship between early maladaptive schemas and compulsive sexual behaviors in a substance-dependent population. (3rd July 2016) - Elmquist, JoAnna; Shorey, Ryan C.; Anderson, Scott; Stuart, Gregory L.
Abstract: Past research has consistently demonstrated high co-occurrence between substance use disorders (SUDs) and compulsive sexual behaviors (CSBs). Numerous studies have also indicated that maladaptive core beliefs and early maladaptive schemas (EMS) are prevalent among individuals with SUDs and CSBs. However, research has yet to examine the relationship between EMS and CSBs among substance-dependent populations. Thus, the purpose of the current study was to examine this relationship in a sample of 198 men and 62 women in residential treatment for SUDs. Findings demonstrated that the five EMS domains were positively associated with CSBs. Results further demonstrated that patients meeting the cutoff score for CSBs scored significantly higher than patients not meeting the cutoff score for CSBs on the EMS domains of disconnection/rejection, impaired autonomy, and impaired limit . These findings suggest that there is an important and significant relationship between EMS and CSBs among adults in substance use treatment. Results from the current study indicate that EMS may provide a potentially important focus for treatment, particularly among individuals with co-morbid CSBs and SUDs. Given the preliminary nature of this study, continued research is needed to replicate and extend the findings from the current study.